Phylogenetic Analysis and Antimicrobial Resistance of Escherichia coli Isolated from Diarrheic Piglets - Tumlam, Uma M.; Pawade, Mrunalini M.; Muglikar, Dushyant M.; Desai, Dhruv N.; Kamdi, Bhupesh P. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Escherichia coli is one of the major causative agents of diarrhea in neonatal piglets worldwide. The present study was conducted toexamine the occurrence of E. coli carrying virulence genes and antibiotic resistance associated with piglet diarrhea in and around Shirwal,District Satara. 30 fecal samples were randomly collected from the piglets with history of diarrhea for the isolation of E. coli followed byscreening of virulence genes among the isolates by specific PCR. Further E. coli isolates were subjected to study phenotypic antibioticresistance by disc diffusion method. The overall occurrence of E. coli was 40% (12/30). On molecular characterization, all the E. coliisolates were found positive for 16S ribosomal RNA gene. The highest antibiotic resistance was found for Amikacin (100%) followed byCloxacillin/Clavulate, Chloramphenicol, Enrofloxacin, Gentamicin and Metronidazole.
Keywords: : Antibiotic drug resistance; Phylogenetic analysis; Piglets Diarrhea